Fabrication and insights into the mechanisms of collagen‐based hydrogels with the high cell affinity and antimicrobial activity. Issue 6 (12th September 2021) - Zhu, Shichen; Yu, Jiehang; Xiong, Shanbai; Ding, Yuting; Zhou, Xuxia; Hu, Yang; Chen, Wenxin; Lin, Yuanli; Dao, Linrui
Abstract: In this study, the adhesive collagen‐based hydrogels with antibacterial ability were prepared via arginine and dopamine modification, and the corresponding characterizations were also performed. A significant increase of N atom content from guanidine group was found via X‐ray photoelectron spectroscopy (XPS), suggesting the guanidine groups were successfully introduced into the systems. The XRD and FTIR patterns indicated that arginine and dopamine did not interrupt the intact triple‐helix conformation of collagen. Both the thermal stability and dynamic modulus of collagen hydrogels first increased and then decreased with the rising introduction of arginine. The increasing attachment of arginine retarded the further aggregations of collagen molecules due to the enhanced electrostatic repulsion, which was also confirmed by the microstructure observed by SEM. The antimicrobial activity of hydrogels modulus intensified significantly with the initial introduction of arginine (0.07 ~ 0.28 mM) ( p  < 0.05) via the measurements of inhibition zone diameter and OD260 value. However, the further addition of arginine did not result in the significant changes in the antibacterial performance. The biocompatibility of collagen hydrogels was not compromised, while the cell adhesiveness was improved. This work may provide a new strategy for the design of collagen‐based antibacterial hydrogels for the wound dressing applications. Abstract : In this study, the adhesive collagen‐based hydrogels with antibacterial ability were prepared via arginine and dopamine modification. This work may provide a new strategy for the design of collagen‐based antibacterial hydrogels for the wound dressing applications.